(untitled) (International Journal of Engineering and Computer Science, 2014)
In this paper a new window function is implemented based on Blackman window function. Tthis window provides higher side lobe attenuation comparison to Hamming window, Hanning window and Blackman window. The width of the main-lobe is slightly greater than Hamming window function and Hanning window function, but slightly less than Blackman window function. In this paper FIR filters are design by using this new window function.